THE EFFECT OF APPLICATION OF READING ALOUD ON SENIOR HIGH SCHOOL STUDENTS’ SPEAKING ABILITY - Sugandi, Bastian; Asih, Nirmala (Universitas Borneo Tarakan, 2019)
This research aimed to find out the effect of the application of reading aloud to improve students’ speaking ability at grade X of SMA Bina Mulya Bandar Lampung 2019. Reading aloud was used to help the students to improve their speaking ability and make them enjoyed in learning English. Data were collected with a pre-test, treatment and post-test. Then, they were analysed with t-Test for two group design. Treatment using reading aloud was administered to experimental group, while control group received technique which was usually used by the teacher. Data analysis was attempted by using t-Test for two group design. Based on the computation, t-value: 7.61 was bigger than p-value in 1%: 2.68 and 5%: 2.01. Therefore, the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. I concluded that there was an effect of the application of reading aloud to improve students’ speaking ability.